2016
DOI: 10.1016/j.ymben.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic engineering of Cupriavidus necator for heterotrophic and autotrophic alka(e)ne production

Abstract: Alkanes of defined carbon chain lengths can serve as alternatives to petroleum-based fuels. Recently, microbial pathways of alkane biosynthesis have been identified and enabled the production of alkanes in non-native producing microorganisms using metabolic engineering strategies. The chemoautotrophic bacterium Cupriavidus necator has great potential for producing chemicals from CO2: it is known to have one of the highest growth rate among natural autotrophic bacteria and under nutrient imbalance it directs mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(66 citation statements)
references
References 37 publications
2
64
0
Order By: Relevance
“…These enzymes are able to form long-chain aldehydes by reduction of fatty acids bound to acyl carrier protein (ACP) and/or to CoA, the latter case being similar to the CoAdependent aldehyde dehydrogenases described above, but acting on long-chain substrates. Some of the enzymes of this group prefer acylCoA as the substrate, while others act more efficiently on acyl-ACP substrates, so will generate products from CoA-dependent fatty acid beta-oxidation or ACP-dependent fatty acid synthesis pathways, respectively, both of which are being investigated through metabolic engineering [101,102]. Interestingly, some of them are able to reduce fatty acid acyl-CoA/ACP directly to long-chain alcohols, requiring oxidation of two molecules of NAD(P)H, instead of one [103].…”
Section: Ec 121: Aldehyde Dehydrogenasesmentioning
confidence: 99%
“…These enzymes are able to form long-chain aldehydes by reduction of fatty acids bound to acyl carrier protein (ACP) and/or to CoA, the latter case being similar to the CoAdependent aldehyde dehydrogenases described above, but acting on long-chain substrates. Some of the enzymes of this group prefer acylCoA as the substrate, while others act more efficiently on acyl-ACP substrates, so will generate products from CoA-dependent fatty acid beta-oxidation or ACP-dependent fatty acid synthesis pathways, respectively, both of which are being investigated through metabolic engineering [101,102]. Interestingly, some of them are able to reduce fatty acid acyl-CoA/ACP directly to long-chain alcohols, requiring oxidation of two molecules of NAD(P)H, instead of one [103].…”
Section: Ec 121: Aldehyde Dehydrogenasesmentioning
confidence: 99%
“…www.chemsuschem.org concentration of 67.7 gL À1 over ap eriod of 72 h. [13] Lonsdale et al reported as imilarr ecombinant system in which the same SH was coupled to aP 450 monooxygenase in Pseudomonas putida, [17] providing at hreefold increase in yield compared to the uncoupled system, with their reported yields rising from 36 to 101 mg L À1 .W hereas the heterologous co-expression of hydrogenases can be quite complex,t he direct use of C. necator offers the possibility of utilizing nativelye xpressed hydrogenases in their natural environment. [23] In summary,w eb elieve that the system proposed in this work lays important groundwork towards the utilization of the hydrogen-oxidizing C. necator as ar obust biocatalytic platform. Thisa pproach has been used by Grousseau et al forthe productiono f3.4 gL À1 isopropanol.…”
mentioning
confidence: 81%
“…This second amplification was carried out using a forward primer (3) and a reverse primer (4) The ferredoxin‐NADP reductase gene (H16_B0102) was amplified from C. necator H16 genomic DNA using a forward primer (5) and a reverse primer (6) A synthetic ribosome binding site (RBS) sequence was encoded in the forward primers (1) and (5) and thus incorporated upstream of each gene. The RBS sequence (5′‐ AAAGGAGGACAACC ‐3′) was already used in a previous work (Crépin et al, ). The pLC10 plasmid (Crépin et al, ) used as a backbone was digested by Hin dIII and treated with Antarctic phosphatase.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, several pathways were reported for engineering alkane and alkene production derived from fatty‐acid metabolism. Recently, we successfully expressed an engineered alka(e)ne pathway in C. necator based on a cyanobacterial native pathway (Crépin et al, ). In cyanobacteria, two enzymes, an acyl‐ACP reductase (AAR, EC:1.2.1.80) and an aldehyde deformylating oxygenase (ADO, EC:4.1.99.5), constitute the alkane biosynthetic pathway (Figure ) (N. Li et al, ; Schirmer, Rude, Li, Popova, & del Cardayre, ; Warui, Li, Nørgaard, Krebs, & Booker, ).…”
Section: Introductionmentioning
confidence: 99%